Prognostic Implications of Serum Carbonic Anhydrase IX in Clear Cell Renal Cell Carcinoma - Mónica Sanz del Pozo; Cristina Plaza Alonso; Álvaro Linacero Gracia; Ángela Pradilla Dieste; Javier Bascuas Hernández; Victoria Capape Poves; María Mata Orus; Benjamín Gaya Sancho; Laura Zaurín Paniagua; Ángel Borque Fernando; José Manuel Sanchez Zalabardo; Berta Sáez Gutiérrez (Journal of Urologic Oncology)
Purpose The present study aimed at determining the expression of carbonic anhydrase IX (CAIX) in tissue and serum of patients with clear cell renal cell carcinoma (ccRCC) and its relationship with clinical-pathological parameters; assessing CAIX as a marker of progression and survival; and studying the relationship of CAIX concentration in serum before and after surgical intervention. Materials and Methods Immunohistochemistry was used to assess the expression of CAIX in tumor and adjacent healthy renal tissues. The concentration of CAIX in serum was determined using commercial enzyme-linked immunosorbent assay before and 24 hours after radical nephrectomy in 60 patients diagnosed with ccRCC. SPSS ver. 28.0.1.0 was used for descriptive and inferential statistical analysis and graphics. A significance level of 0.05 was considered for all statistical tests performed. Results CAIX expression was positive in 59 of the 60 samples of tumor renal tissue, and negative in the 60 samples of healthy renal tissues. Median serum CAIX concentration was higher before nephrectomy (178.25 pg/mL) than after it (59.30 pg/mL), with a high correlation between pre-and postsurgical measurements (r=0.891). Significant differences were found in CAIX concentration according to the following variables: TNM, tumor stage, Fuhrman nuclear grade, progression, and death. Serum CAIX concentration before nephrectomy correlated with disease progression and overall survival, with a hazard ratio of 4.849 for CAIX values greater than 169.95 pg/mL. Conclusion CAIX expression in tumor renal tissue was specific, but not clinically useful as a prognostic marker. Measurements of CAIX in serum obtained pre- and postsurgical interventions showed good prognostic potential, correlating with clinical-pathological parameters and estimating the risk of progression. Presurgical intervention serum CAIX concentrations higher than 169.95 pg/mL indicated an almost 5-fold increased risk of death.